(3GdQSGdI GdehVMI (B((3aj PcQ SQbGJ CHj GdWjH GdeJfHi hSGbW TYQg(B)s - (3eMeO Hf GdMSf Hf GdeXaQ GdMGJej GdHZOGOj , CHh Ydj,J (B388 (3g` s; (3CHhGdWjH CMeO Hf GdMSjf Hf GdMSf Hf YHO GdUeO Hf GdLYaj Gdchaj GdeYQha H` CHj GdWjH GdoeJfHj,J (B354 (3g` s ((3eMeO Hf YHOGdedc Hf YSGcQ GdTGaYi GdHYdHci s)
(3ChdgG (B:s
(3Ef eYGfi GdCOH Ef cGfJ YGWdI GdCWdGd eSJjdI GdMGd OGKQg GdYQUGJ YGJjI GdeYGde hGdBjGJ s
(3BNQgG (B:s
(3CaQO HPdc cJGHkG hCSJbUjg hGfJgi Edi GdZGjI GdJi JHdZgG GdbOQI ajg HMhd Gddg hbhJg haVdg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3hHgGeTgG HYV GdTQhM hGdJYdjbGJs
(3hHChdgG agQSs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs